Vietnam's Petroleum Sector : Technical Assistance for the Revision of the Existing Legal and Regulatory Framework - World Bank (Washington, DC, 2014)
The oil and gas potential of Vietnam's continental shelf remains relatively unexplored compared with that of its neighbors, including China, Indonesia, Malaysia, and Thailand. A number of factors affect the decision to undertake petroleum investments: geology, geography, geopolitics, and investment climate. Host governments cannot control the first three factors. However, they do control the investment climate, and the legal and contractual framework and the petroleum fiscal system are key factors to be considered in the competition among governments for access to investment capital. Despite intense efforts to attract international oil companies to explore the country's sedimentary basins, including incentive terms contained in a 1998 decision of the prime minister, drilling activity has remained modest in recent years. The government requested technical assistance from ESMAP for revision of its petroleum legal regime so that it might become a modern legal and regulatory framework for the petroleum sector and attract foreign investment to develop its hydrocarbon reserves. The project team evaluated and identified international best practice in the areas of petroleum regimes to develop its recommendations to Vietnam. They recommended strengthening of the legal, regulatory, and contractual framework based on three cornerstones: the Petroleum Law, the Regulations (or, as they are called in Vietnam, the Decrees), and a Model Contract based on production-sharing agreements. Recommendations were provided to the government of Vietnam in a series of meetings, workshops, and reports.